2015
DOI: 10.1080/13607863.2015.1078284
|View full text |Cite
|
Sign up to set email alerts
|

Age does not matter: Memory complaints are related to negative affect throughout adulthood

Abstract: Objectives Memory complaints are present in adults of all ages but are only weakly related to objective memory deficits, raising the question of what their presence may indicate. In older adults, memory complaints are moderately related to negative affect, but there is little research examining this relationship in young and middle-aged adults. This study examined whether memory complaints and negative affect were similarly related across the adult lifespan and in adults with varying levels of objective memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 63 publications
2
25
0
2
Order By: Relevance
“…Furthermore, some studies also convey the idea that subjective memory complaints are more frequently reported in aged groups (e.g., Dobbs & Rule, 1987; Ponds, Commissaris & Jolles, 1997). In the light of this evidence, firstly, some studies reveal that subjective memory complaints do not increase with age (e.g., Mendes et al, 2008; Rowell et al, 2016; Smith et al, 2000), and the results found here lend evidence to such pattern. Secondly, it is important to consider that the literature has also been showing weak associations between objective and subjective measures of memory functioning (Mendes et al, 2008; Paquet et al, 2017; Thompson et al, 2015; Uttl & Kibreab, 2011), hence the same pattern across age may not be verified for both type of measures.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, some studies also convey the idea that subjective memory complaints are more frequently reported in aged groups (e.g., Dobbs & Rule, 1987; Ponds, Commissaris & Jolles, 1997). In the light of this evidence, firstly, some studies reveal that subjective memory complaints do not increase with age (e.g., Mendes et al, 2008; Rowell et al, 2016; Smith et al, 2000), and the results found here lend evidence to such pattern. Secondly, it is important to consider that the literature has also been showing weak associations between objective and subjective measures of memory functioning (Mendes et al, 2008; Paquet et al, 2017; Thompson et al, 2015; Uttl & Kibreab, 2011), hence the same pattern across age may not be verified for both type of measures.…”
Section: Discussionsupporting
confidence: 73%
“…Secondly, it is important to consider that the literature has also been showing weak associations between objective and subjective measures of memory functioning (Mendes et al, 2008; Paquet et al, 2017; Thompson et al, 2015; Uttl & Kibreab, 2011), hence the same pattern across age may not be verified for both type of measures. Indeed, other variables such as mood seem to be particularly correlated with self-report measures of memory functioning (Bassett & Folstein, 1993; Pearman, 2009), and this result holds true for younger and middle-age adults (Mendes et al, 2008; Rowell et al, 2016). While objective tests seem to provide a more reliable approximation to memory functioning, subjective measures allow to explore other factors, such as memory self-efficacy, self-awareness and mood (Roche, Fleming & Shum, 2002; Rönnlund et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…[25][26][27][28] Others, however, found no such increase. 24,[29][30][31] It is also largely unknown, whether other sociodemographic (gender, educational attainment) and psychological variables (depressive symptomatology, neuroticism, cognitive performance), which have been identified in previous research as potentially influencing subjective memory/cognitive complaints, 11,24,32 are also relevant for the other cognitive domains.…”
Section: Introductionmentioning
confidence: 99%
“…Депрессивное состояние приводит к негативному самовосприятию, что, в свою очередь, может усиливать общую тенденцию сообщать о различных проблемах. Связь между депрессивной симптоматикой, чувством тревоги и СКС подтверждается как в клинических, так и в популяционных исследованиях [16][17][18][19][20][21][22][23][24]. В нашей работе не обнаружено значимой связи между наличием легких и умеренных тревожно-депрессивных проявлений и когнитивным статусом пациентов с ЛКС [5].…”
unclassified
“…Проведенное нами сравнение подгрупп пациентов с СКС и легкими эмоционально-аффективными расстройствами и без таковых значимых различий в показателях когнитивных функций не обнаружило [6]. В крупном американском популяционном исследовании установлено, что эта ассоциация была сходной в разных возрастных группах у взрослых пациентов [18]. В датском исследовании выявлено, что у лиц моложе 65 лет с аффективным расстройством имелись более выраженные субъективные когнитивные симптомы, чем у пациентов других групп с нарушениями памяти (деменция, УКН, группа здоровых без когнитивных нарушений) [25].…”
unclassified